Homelessness as a Social Problem - Socio-pathological Phenomenon - Qualitative Analysis - Tvrdoň, Miroslav; Lojan , Radoslav; Máhrik, Tibor; Zaharia, Stefan; Davydova, Vladimirovna Ekaterina (Journal of Education Culture and Society, 2022)
Aim. In qualitative research, the authors identify the most frequent cases of homeless people staying on the street and identify general prejudices against homeless people who come into direct contact with the public.Methods. The study analyses and interprets the risk aspects of the real life of the homeless. Through qualitative research based on open coding, the creation of a system of categories, and analytical induction, the authors established a final hypotheses.Results. Studies confirm that homelessness affects not only the life of an individual, but also points to the experience of homeless society and the image of the homeless today. The authors analyse and identify the opinions of social workers who have experience with this target group.Conclusion. The scholarly and professional opinions and contributions in this study highlight the strength and diversity of homelessness. By conducting qualitative research, they identify prejudices against the homeless and the causes that contribute to homelessness.